Acceptance of local community towards mosque tourism in Melaka strait - Aman, Rabi'atul Adawiyah; Saad, Mazni (Kulliyyah of Languages and Management, 2021)
Purpose: The paper aims to examine the local community' acceptance of Melaka Tengah towards mosque tourism in the Melaka Strait Mosque. Methods/Design/approach: The method used in this study was purposive sampling, which was under non-probability sampling. The data were collected through a questionnaire distributed to the local communities in Melaka Tengah, especially those in the Melaka Straits Mosque. Findings: The study's findings revealed that the majority of the local communities in Melaka Tengah have welcomed the tourists to the Melaka Straits Mosque as it has become one of the tourist attractions in Melaka Tengah study perceived social factor followed by an economic factor as positive findings. Implication: The local communities in Melaka Tengah were strongly agreed that Melaka Straits Mosque acted as a tourism site, and they were aware of its importance since it has brought many benefits to them. Besides, the local communities in Melaka Tengah were interested in investing in the development of mosque tourism in Melaka Tengah, especially the Melaka Straits Mosque. It is hoped that there will be more tourism development in Melaka Straits Mosque in the future.